Lasersko sintranje orodja za tlačno litje aluminija - Dolinšek, Slavko (Strojniški vestnik, 2006)
In this paper some results from using a DMLS (direct metal laser sintering) rapid-tooling solution for aluminum die-casting are presented. The product chosen for the investigation was a car safety-belt strap winder (an application for the automotive industry), and according to the requirements ofthe prototype tools, we have adapted the construction of the classic tools and made some improvements to the material and the sintering process. The comparative-value analysis with classical tooling has shown that the time of production with the DMLS process is considerably shorter. The final investigation was focused on the industrial testing of the DMLS, followed by the tool analysis after die-casting to confirm the research goal, i.e., 5,000 practical parts produced.
Keywords: orodja; aluminij; aluminum; lasersko sintranje; tlačno litje